Sosiofonologi Leksikon Serapan dari Bahasa Arab yang Berfonem Asal ث , ذ, ,ص ض , dan ظ dalam Bahasa Indonesia - Imam Baehaqie (Ranah: Jurnal Kajian Bahasa, 2022)
The aims of this study are to describe the form of the variation of the Arabic loan lexicon in Indonesian on social media, and to explain the possible social factors that cause its emergence. This research approach is a qualitative sociophonological approach. The data of this research is in the form of an absorption lexicon from Arabic in Indonesian. The data source of this research is speech on social media mass accounts (Facebook) in the religious domain which is thought to contain the Indonesian language lexicon which is absorbed from Arabic. The data collection method used is the listening method and the analysis method is the matching method. The method of presenting the results of data analysis is the informal method. From the results of data collection found 150 absorption lexicon. Based on the results of the discussion, it is stated that the variation of the absorption lexicon from Arabic in Indonesian is mostly found in lexicon containing the original phonemes ﺙ, ذ, ص, ض, and ظ and both in the first, second, third, and so on syllables, both in the onset position, nucleus, and coda. The possible factors causing the variation of the absorption lexicon are (1) a lack of understanding of the current Arabic-Latin transliteration guidelines; (2) the flexibility of the speaker's attitude in language; (3) differences in socio-humanities background: education level, field of science, and field of profession (livelihood); (4) speech channel. The results of this study can be useful as a contribution of ideas in language planning and Indonesian language teaching planning, both for native speakers and foreign speakers. AbstrakTujuan penelitian ini adalah mendeskripsi wujud variasi  leksikon serapan dari bahasa Arab dalam bahasa Indonesia pada media social, dan menjelaskan kemungkinan faktor  sosial penyebab kemunculannya. Pendekatan penelitian ini adalah pendekatan sosiofonologis kualitatif. Data penelitian ini berupa leksikon serapan dari bahasa Arab dalam bahasa Indonesia. Sumber datanya adalah tuturan pada akun-massa media sosial (Facebook) dalam ranah agama yang diduga memuat leksikon bahasa Indonesia yang diserap dari bahasa Arab.  Metode penjaringan data yang digunakan adalah metode simak dan metode analisisnya adalah metode padan. Adapun metode penyajian hasil analisis datanya adalah metode informal. Dari hasil penjaringan data ditemukan 150 leksikon serapan. Berdasarkan hasil pembahasan dinyatakan bahwa variasi leksikon serapan dari bahasa Arab dalam bahasa Indonesia banyak ditemukan pada leksikon-leksikon yang memuat fonem asal ﺙ, ذ, ص, ض, dan ظ baik dalam silabel pertama, kedua, ketiga, maupun seterusnya, baik dalam posisi onset, nuklus, maupun koda.  Adapun kemungkinan faktor penyebab kemunculan variasi leksikon serapan tersebut adalah: (1) kurangnya pemahaman terhadap pedoman transliterasi Arab-Latin yang masih berlaku; (2) kelenturan sikap penutur  dalam berbahasa; (3) perbedaan latar sosial-humaniora: jenjang pendidikan, bidang ilmu, dan bidang profesi (mata pencaharian); (4) saluran tutur. Hasil penelitian ini dapat bermanfaat sebagai sumbangan pemikiran dalam perencanaan bahasa dan perencanaan pengajaran bahasa Indonesia, baik untuk penutur jati maupun penutur asing.